Anatomical investigation of the slender catshark Schroederichthys tenuis Springer, 1966, with notes on intrageneric relationships (Chondrichthyes: Carcharhiniformes: Scyliorhinidae) - Gomes, Ulisses L.; Peters, Gerhard O.; De Carvalho, Marcelo R.; Gadig, Otto B. F. [UNESP] (My University, 2006)
The slender catshark Schroedericthys tenuis Springer, 1966, originally described from two immature males, is redescribed on the basis of 12 specimens of both sexes, juveniles and adults (as well as the holotype and paratype). The supplementary specimens were collected off the northern coast of Brazil between Amapá and Pará states. Aspects of its external morphology, color pattern, dermal denticles, dentition, vertebral counts, and the cephalic, clasper and pectoral fin skeleton are described in detail and fully illustrated. These features are compared with those of congeneric species. Our observations support preliminary results of work in progress that S. maculatus Springer, 1966, S. tenuis and S. saurisqualus Soto, 2003 form a monophyletic group, mostly on the basis of neurocranial morphology, and that S. bivius (Smith, 1838) and S. chilensis (Guichenot, 1848) should be removed from Schroederichthys. Copyright © 2006 Magnolia Press.
Keywords: Anatomical description; Phylogenetic relationships; Schroedericthys tenuis; Scyliorhinidae; Western South Atlantic Ocean; Carcharhiniformes; Chondrichthyes; Schroederichthys; Schroederichthys bivius; Schroederichthys chilensis; Schroederichthys maculatus; Schroederichthys saurisqualus; Schroederichthys tenuis